REVOLUTIONIZING AND DEMOCRATIZING DIGITAL LEARNING: A CASE STUDY OF THE TRANSFORMATIVE IMPACT OF MASSIVE OPEN ONLINE COURSES IN CREATIVE EDUCATION - Srinivasan, Narendhar; Resmi CP; Rebera, Daisy Roshan; Rajalakshmi A (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the transformative influence of Massive Open Online Courses (MOOCs) on creative education, focusing on the democratization of knowledge and analyzing student engagement in virtual classrooms. The primary objective is to investigate how MOOCs democratize knowledge for creative learners, emphasizing the global accessibility, flexibility, and cost-effectiveness of online courses. In-depth interview with working professionals and online learners constitutes the methodology, allowing participants to share experiences and uncover the emotional and personal aspects of their educational journey. Findings reveal that creative learners prefer MOOCs for their flexibility, allowing learning at one’s own pace, replaying specific sections, and accessing diverse courses at a lower cost compared to traditional platforms. The inclusivity of MOOCs enables interdisciplinary learning, expanding domain knowledge and fostering collaboration among learners from various backgrounds. The study underscores the practical benefits of increased job opportunities and diverse skill acquisition. In conclusion, this research highlights the transformative impact of MOOCs, democratizing education for creative learners and offering a paradigm shift in educational delivery. The findings emphasize the need for transparent course information and recorded solutions to enhance the overall learning experience in the evolving landscape of online education.